Stem cell biology in thyroid cancer: Insights for novel therapies - Bhatia, Parisha (Baishideng Publishing Group Inc, 2014)
Currently, thyroid cancer is one of the most common endocrine cancer in the United States. A recent involvement of sub-population of stem cells, cancer stem cells, has been proposed in different histological types of thyroid cancer. Because of their ability of self-renewal and differentiation into various specialized cells in the body, these putative cells drive tumor genesis, metastatic activity and are responsible to provide chemo- and radioresistant nature to the cancer cells in the thyroid gland. Our Review was conducted from previously published literature to provide latest apprises to investigate the role of embryonic, somatic and cancer stem cells, and discusses the hypothesis of epithelial-mesenchymal transition. Different methods for their identification and isolation through stemness markers using various in vivo and in vitro methods such as flow cytometry, thyrosphere formation assay, aldehyde dehydrogenase activity and ATP-binding cassette sub-family G member 2 efflux-pump mediated Hoechst 33342 dye exclusion have been discussed. The review also outlines various setbacks that still remain to target these tumor initiating cells. Future perspectives of therapeutic strategies and their potential to treat advanced stages of thyroid cancer are also disclosed in this review.